(2-Nitroethyl)benzene: a major flower scent from the Japanese loquat Eriobotrya japonica [Rosales: Rosaceae]. Issue 8 (3rd August 2014) - Kuwahara, Yasumasa; Ichiki, Yayoi; Morita, Masashi; Asano, Yasuhisa
Abstract: (2-Nitroethyl)benzene was identified as a major component of the flower scent of the Japanese loquat Eriobotrya japonica [Rosales: Rosaceae], together with p -methoxybenzaldehyde and methyl p -methoxybenzoate. The corresponding volatiles from chopped leaves did not contain these three compounds. This is the first time that 1-nitro-2-phenyl-ethane has been demonstrated to be a natural product among Japanese plants, although two Japanese millipedes are known to possess the same aromatics.